PENGEMBANGAN USAHA MADU TRIGONA DI BELITUNG - Mei Ie; Atalya Fransiska (PROSIDING SERINA, 2021)
During a pandemic, most people believe that honey is one type of health drink that can increase immunity. Currently many honey producers run trigona honey business. Trigona honey is produced from lebah honey Trigona,which is a unique bee, which has no sting. Every product produced from these bees, of course, has high benefits for health. Not only for people who consume, the products produced can certainly be useful also for honey producing producers. One of them is to generate income from the production of honey. However, behind the benefits and impacts that can be provided by Trigona honeybees, there are problems that are often faced by partners or honey producers, It is related to product marketing. Often the technique of marketing honey is done is to market it directly into the hands of consumers, not infrequently also products are marketed in the hands of consumers. bottle packaging without a specific brand and size. This can certainly reduce consumer loyalty in buying products. Thus the purpose of this abdimas activity is to develop Trigona product marketing strategies in Belitung in order to reach a wider market. The method of carrying out activities is carried out through entrepreneurship and mentoring seminars conducted online. In the end, the activities are done well and can have a positive impact on the partner side. The partner states that they are more understanding about entrepreneurship and business development strategies, especially marketing strategies that can be implemented. Thus it is expected that partners can expand the existing consumer market as well as improve their business performance.